The Effectiveness of Cooperative Learning Method Type Talking Stick in Improving Vocabulary Memorization of the VIII class Students of MTs Al-Kautsar Kao - S Syamsia; Nurfaija Rusdy (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2021)
The aim of this research is to know the effectiveness of students in memorizing English vocabulary through cooperative learning model using talking stick. Vocabulary is important to be master since someone can’t talk without knowing vocabulary. At some junior schools the students have a low mastery of vocabulary. This research uses the Classroom Action Research; this research was conducted at Mts Al-Khautsar Kao. The subjects of this research were students of class VIII, totaling 27 students consisting of 14 girls and 13 boys. The research has some techniques and some instruments to gain both qualitative and quantitative data. The techniques are observation, interview, testing, and documenting study. To analyze the data, the researcher started by doing reflection of the cycles of the study. This means that the data were analyzed continually since the implementation of the action began. As this research was a classroom action research, therefore, to avoid subjectivity, the researcher involved the research members to find their perceptions, opinions and suggestions in analyzing the data.The result of the reflection in cycle I was not improved so this research continues in cycle II. Based on the students’ result in cycle II, it was found out that the students‟ vocabulary score was improved. It indicated that the use of talking stick technique could encourage and motivate them to retain and enrich their vocabulary.